Forest business incubator - An innovative institution for business development in forestry and agroforestry sector in India - Parthiban, KT; Krishna Kumar, N; Cinthia Fernandez, C (Indian Forester, 2020)
The demand for wood and wood products in India is increasing at an alarming rate but there is no concomitant plantation development to satisfy the demands barring few exceptions like pulp and plywood plantation developmental activities. The legal and policy guidelines have restricted the felling operations in natural forest, thus results in decline in wood supply. It is also directed that the wood based industries should derive their own raw material resources by establishing suitable linkages with farmers and other stakeholders. This besides, wide range of forestry products like composite wood, value added products like briquettes, pellets, activated charcoal, carbon, medicinal products, gums, resins, oils, etc., are also in huge demand which necessitated suitable technology development and the associated value addition process. All these activities underscore the need for skill development from production to consumption system in forestry and agroforestry sector in order to treat forestry as a commercial and business enterprise. However as on date, there is no institutional mechanism to cater to the needs of skill and expertise development and the associated forestry based entrepreneurship development in the country. Against this backdrop, the Forest College and Research Institute of Tamil Nadu Agricultural University has conceived an innovative idea of forestry based business incubation and established India’s first Agroforestry Business Incubator and involved in forestry and agroforestry based business entrepreneurship development. The establishments, activities and achievements of this innovative and pioneer institutional mechanism are discussed in this manuscript for adoption and replication both within and outside the country